2015
DOI: 10.1042/bst20140281
|View full text |Cite
|
Sign up to set email alerts
|

Post-translational myristoylation at the cross roads of cell death, autophagy and neurodegeneration

Abstract: In a little more than a decade, post-translational myristoylation (PTMyr) has become an established post-translational modification during cell death. It involves the addition of the fatty acid myristate to newly exposed N-terminal glycines following caspase cleavage. It promotes membrane binding and relocalization of functional protein domains released by caspase cleavage during apoptosis, or programmed cell death. However, as the requirement of caspase cleavage has expanded beyond just cell death, it has bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…Although the majority of N-myristoylated proteins undergo fatty acylation during protein translation, a second class of NMT substrates that are N-myristoylated post-translationally has been uncovered[15, 16]. During apoptosis, caspase-mediated cleavage between Asp-Gly exposes glycine at the N-terminus of the newly cleaved product.…”
Section: N-myristoylationmentioning
confidence: 99%
“…Although the majority of N-myristoylated proteins undergo fatty acylation during protein translation, a second class of NMT substrates that are N-myristoylated post-translationally has been uncovered[15, 16]. During apoptosis, caspase-mediated cleavage between Asp-Gly exposes glycine at the N-terminus of the newly cleaved product.…”
Section: N-myristoylationmentioning
confidence: 99%
“…The posttranslational myristoylation of protein was first reported in 2000, to show that N-myristoylation of BID after its being cleaved by caspase 8 targets the myristoylated BID to mitochondrial membrane that augments the cellular pro-apoptotic activity (Figure 4) (4). As initiation of apoptosis is characterized by caspase-mediated proteolytic cleavage at the preferred glycine (85, 86), it is highly plausible that myristoylation might be the common posttranslational modification following caspase-mediated proteolytic cleavage (87). It then suggests that the posttranslational myristoylation may play a key role in cell survival and apoptosis.…”
Section: Myristoylation Regulates Mitochondrial Calcium Release Activmentioning
confidence: 99%
“…Heretofore, only BID and p21-activated kinase 2 are the known substrates of posttranslational myristoylation. With the in silico prediction analysis, coupled to an overexpression system, other substrates of posttranslational myristoylation (including but not limited to gelsolin B cell receptor-associated protein 31 and YTH domain family protein) have been discovered (4, 87, 88). These in vitro identified substrates were validated using a robust proteomic technique that uses new NMT inhibitors to confirm myristoylation (89).…”
Section: Myristoylation Regulates Mitochondrial Calcium Release Activmentioning
confidence: 99%
“…We have shown that cleavage at D552 is required to release a newly exposed N-terminal glycine at position 553 (G553) that is subsequently posttranslationally myristoylated (16)(17)(18). Myristoylation involves the covalent addition, via an amide bond, of the saturated fatty acid myristate to Nterminal glycines that directs proteins to membranes (19,20). We also recently discovered a naturally occurring missense mutation at this site wherein the essential glycine is substituted to a glutamate, thereby blocking myristoylation (17).…”
mentioning
confidence: 99%